Herbicides, Physiology of Action, and Safety 2015
DOI: 10.5772/61616
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring the Environmental Quality by Bees

Abstract: Modern farming techniques have increased the crop yield, but natural habitats of the pollinator were destroyed, affecting their populations compared to native vegetation. A simple, low-cost, and efficient way to determine the presence of insecticide residues from farming is the honeybee as a bioindicator. However in Brazil, there is another species of bee, the stingless bees. The insecticide toxicity analyses the beneficial insect species as pollinators which are performed to the Apis mellifera. Stingless bees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(58 reference statements)
1
2
0
1
Order By: Relevance
“…Laurino et al performed oral test with thiamethoxam and found it to be lethal to adult A. mellifera bees following exposure up to 72 h from the start of the test. These data reinforce that stingless bees are more sensitive than honey bees when exposed to pesticides …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Laurino et al performed oral test with thiamethoxam and found it to be lethal to adult A. mellifera bees following exposure up to 72 h from the start of the test. These data reinforce that stingless bees are more sensitive than honey bees when exposed to pesticides …”
Section: Discussionsupporting
confidence: 80%
“…Among the threats to bees, disintegration and loss of habitat, migratory apiculture, high levels of parasites, and intensive use of pesticides are highlighted …”
Section: Introductionmentioning
confidence: 99%
“…O declínio de polinizadores incita graves consequências para os ecossistemas naturais, visto que, a dependência da polinização para plantas florais varia entre 78% e 94% em ecossistemas temperados e tropicais (OLLERTON, WINFREE e TARRANT, 2011). Dentre os elementos que ameaçam a ação polinizadora das abelhas, encontra-se a fragmentação do habitat, alterações climáticas, espécies invasoras, diminuição do interesse na apicultura, patógenos e pesticidas (JOHNSON et al, 2010;MAINI, MEDRZYCKI, PORRINI, 2010;VANBERGEN et al, 2013;RUVOLO-TAKASUSUKI et al, 2015;MAGGI et al, 2016;SHEFFIELD, NGO, AZZU, 2016;REQUIER, 2020).…”
Section: Declínio Dos Polinizadores E Mecanismos De Ação Dos Pesticidasunclassified
“…These stingless bees are also important pollinators of native species of plants (Giannini et al, 2020), mainly strawberries (Abrol, Gorka, Ansari, Al-Chamdi, & Al-Kahtani, 2019). During foraging in agricultural regions, these pollinators come into contact with pesticide residues, which can compromise pollination, development of colonies and the bee products (Ruvolo-Takasusuki et al, 2015;Silva, Melo, & Blanco, 2016), but as the effects of pesticides in this species are limited, toxicological evaluations are still needed.…”
Section: Introductionmentioning
confidence: 99%